Parenting in the city: effects of urbanization on incubation behaviour and egg temperature in great tits, Parus major. (December 2022) - Hope, Sydney F.; Hopkins, William A.; Angelier, Frédéric
Abstract : With 68% of the world's population expected to live in cities by 2050, it is crucial to understand how animals respond to urbanization. Urban areas are associated with changes in microclimate, light, noise and human activity, which can affect animal physiology, behaviour and fitness. In particular, urbanization may affect how parents allocate time and energy between parental care and self-maintenance. In birds, a critical aspect of parental care is incubation, where parents must maintain egg temperatures for successful offspring development. However, incubation is energetically costly, and anthropogenic disturbances may affect parental decisions related to this cost. Determining whether urbanization affects incubation is crucial for understanding the differences between urban and nonurban populations in their reproductive performance and fitness. We measured incubation behaviour and egg temperature in one urban and one forest population of great tits, a uniparental incubator, using temperature loggers. We found that, compared to forest females, urban females spent more time incubating, took shorter off-bouts and ended their last daily off-bouts at a later hour. Furthermore, time spent off the nest, the number and duration of off-bouts and daily start of activity were related to ambient temperature; start of activity was related to clutch size; and time spent off the nest was related to the day of incubation. Despite urban females spending more time on the nest, eggs of both forest and urban females experienced relatively similar average egg temperatures, and urban eggs tended to experience greater variability in egg temperature. Furthermore, there were no differences between sites for any fitness-related offspring variable. Our results suggest that urbanization can influence the thermal environment of developing avian offspring by causing urban adults to be inefficient incubators through increased activity off the nest in the evening, differences in nest insulation and/or suboptimal incubation behaviour compared to forest counterparts. Highlights: Urbanization appears to influence parental incubation behaviour of great tits. Urban birds spent more time warming their eggs compared to birds in the forest. However, outcomes for offspring were similar. Urban eggs and forest eggs experienced similar temperatures.